Reformulation of Virtual Advocate Regulations in a Legal Certainty-Based Digital Legal Services System in Indonesia - Rusdi; Zainal Arifin Hoesein (Yayasan Pendidikan Tanggui Baimbaian, 2026)
The development of Legal Technology (LegalTech) and Artificial Intelligence has driven the transformation of legal services towards virtual advocacy practices. However, the Indonesian legal system does not yet have regulations that specifically regulate the concept, scope, service standards, or responsibilities of the virtual advocacy profession, resulting in a legal vacuum and uncertainty in the provision of digital legal services. This study aims to analyze the legal vacuum surrounding virtual advocacy and formulate a concept for reforming these regulations based on legal certainty in Indonesia. The study employs a normative juridical method with a statutory and conceptual approach. Legal materials are analyzed prescriptively through grammatical, systematic, and teleological interpretations. The results show that Law Number 18 of 2003 concerning Advocates, Law Number 1 of 2024 concerning Electronic Information and Transactions, Law Number 27 of 2022 concerning Personal Data Protection, and the Indonesian Advocates Code of Ethics do not yet accommodate virtual advocacy practices. The proposed reforms include establishing a legal definition for virtual advocates, setting limits on the use of Artificial Intelligence, electronic identification standards, client data protection, transparency in technology use, professional accountability mechanisms, and regulatory harmonization to ensure legal certainty in digital legal services.